1994
DOI: 10.1039/c39940002251
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective hydroformylation with the chiral bidentate P,N-ligand 2-[1-(1S,2S,5R)-(–)menthoxydiphenylphosphino]pyridine cationic rhodium(I) complexes

Abstract: Cationic rhodium(1) complexes containing the new chiral bidentate P,N ligand 2-[l-(1 S,2S,5R)-(-)menthoxydiphenylphosphinolpyridine are prepared and used successfully in the enantioselective hydroformylation of olefinic substrates, styrene, 2-vinylnaphthalene, methylacrylate and vinylacetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Recent reports on unusually stable C,N-, [9] C,P-, [10] N,S-, [11] N,P-, [12] and S,S'- [13] chelating ocarboranyl metal complexes seem to imply that the rigid chelate conformation and the ortho-carboranyl ligand backbone might be ideal for the stabilization of possible metal intermediates in organometallic reactions. Therefore, the design of such a ligand system containing one functional group strongly bound to a transition metal center and another one coordinatively labile has been of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Recent reports on unusually stable C,N-, [9] C,P-, [10] N,S-, [11] N,P-, [12] and S,S'- [13] chelating ocarboranyl metal complexes seem to imply that the rigid chelate conformation and the ortho-carboranyl ligand backbone might be ideal for the stabilization of possible metal intermediates in organometallic reactions. Therefore, the design of such a ligand system containing one functional group strongly bound to a transition metal center and another one coordinatively labile has been of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is considerable current interest in hybrid P/N ligands and a search in the Cambridge Structure Database revealed that although a vast number of Groups 9-10 complexes with nitrogen and phosphorus ligands have been characterised structurally, only a relatively small number of Pd(II) cations and Rh(I) cations [54][55][56][57][58][59][60][61][62][63][64][65] containing bidentate N(sp 2 )-P(sp 3 ) donors are reported. Since bulky substituents at the aryl groups of N(sp 2 ) donors have been found to strongly influence the catalytic activity and selectivity of Group 10 complexes [66], it is surprising that no Rh(I) complexes of ligands combining tertiary phosphine donors and (sp 2 )N-aryl donors with bulky ortho substituents have been structurally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in the case of cyclic starting materials, stereoselectivity plays no role. [6a] Vinyl acetates are valuable substrates for polymerizations, are versatile acylating agents, and can be applied in cyclo-propanations, [7] cycloaddition procedures, [8] asymmetric hydrogenations, [9] the preparation of enamides, [10] hydroforA C H T U N G T R E N N U N G myl-A C H T U N G T R E N N U N G ation reactions; [11] furthermore, they can be used as aryl halide equivalents. [12] However, the use of vinyl benzoates has rarely been investigated; in particular, they have only been used in enantioselective cyclopropanation reactions.…”
mentioning
confidence: 99%